Снігоборотьба на залізницях Росії (друга половина ХІХ – початок ХХ ст.) - Потапенко, Л.Л. (Питання історії науки і техніки, 2009)
Расширение строительства железных дорог в России на ее юго-западные районы усугубило проблемы, связанные со снежными заносами. Поэтому во второй половине XIX- начале XX века широко разворачиваются теоретические исследования и разработка практических мероприятий, связанных с изучением этого явления, а также с предотвращением заносов и борьбой с последствиями их образования. В статье изложены основные результаты указанных работ. Expansion of construction of railways in Russia on its southwest areas has aggravated
the problems connected with snow drifts. Therefore in second half XIX-beginning of
XX century theoretical researches and development of the practical actions connected
with studying of this phenomenon, and also with prevention of drifts and struggle against
consequences of their formation are widely developed. In clause the basic results of the
specified works are stated.